2003
DOI: 10.1074/jbc.m304590200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Interleukin-4-induced Class Switch Recombination by a Human Immunoglobulin Fcγ-Fcϵ Chimeric Protein

Abstract: Immunoglobulin E (IgE) is important in mediating human allergic diseases. We tested the hypothesis that a human Ig Fc␥-Fc⑀ bifunctional chimeric protein, GE2, would inhibit IgE class switch recombination (CSR) by co-aggregating B-cell CD32 and CD23. Indeed, GE2 directly inhibited ⑀ germ-line transcription, subsequent CSR to ⑀ and IgE protein production. This CSR inhibition was dependent on CD23 binding and the phosphorylation of extracellular signal-related kinase (ERK), and it was mediated via suppression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
(25 reference statements)
1
13
0
Order By: Relevance
“…6 We have developed and tested a novel Fcc:Fce human bifunctional Ig fusion protein, human IgG-IgE Fc fusion protein (GE2), designed to inhibit basophils, mast cells, and B cells by cocrosslinking FceRI or FccRII (CD23) with FccRs (Fig 1). [7][8][9] However, in those previous experiments, we showed that GE2 inhibits mast cell, basophil, and Langerhans-like cell function under conditions in which the cells in vitro or in vivo had been artificially sensitized with a humanized IgE mAb. 7,8 In the present study we extended the testing of GE2's function to the setting of naturally sensitized nonhuman primates, human basophils and mast cells, and humanized FceRI cells in transgenic mice.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…6 We have developed and tested a novel Fcc:Fce human bifunctional Ig fusion protein, human IgG-IgE Fc fusion protein (GE2), designed to inhibit basophils, mast cells, and B cells by cocrosslinking FceRI or FccRII (CD23) with FccRs (Fig 1). [7][8][9] However, in those previous experiments, we showed that GE2 inhibits mast cell, basophil, and Langerhans-like cell function under conditions in which the cells in vitro or in vivo had been artificially sensitized with a humanized IgE mAb. 7,8 In the present study we extended the testing of GE2's function to the setting of naturally sensitized nonhuman primates, human basophils and mast cells, and humanized FceRI cells in transgenic mice.…”
mentioning
confidence: 59%
“…In addition, other studies have shown that GE2 inhibits B-cell IgE production and human Langerhans cell proallergic activity. 8,9 It should be noted that all the tests conducted thus for were either experiments in vitro or local tests in vivo. The effects of GE2 on inhibiting systemic allergic responses, such as asthma, should be tested when an appropriate animal model is available.…”
Section: Discussionmentioning
confidence: 99%
“…By showing a requirement for the Fc portion of anti-CD23, Yabuuchi et al [26] suggested that IgE suppression occurred through cross-linking CD23 to a Fc R. In addition, it was demonstrated that a primatized anti-CD23 inhibited germline C transcription in B cells [27]. In support of the above studies, a human Ig Fc -Fc bifunctional chimeric protein designed to co-aggregate B cell CD32 and CD23 was shown to inhibit class switch recombination to IgE [28]. In a clinical trial, humanized anti-CD23 (IDEC-152 or lumiliximab) was found to modulate IgE levels [29•].…”
Section: Anti-cd23 Can Either Inhibit or Enhance Ige Productionmentioning
confidence: 90%
“…But it was not clear whether this bispecific Ab acted through an ITIM motif, competed with IgE for binding to FcRI, and/or interfered with the aggregation of IgE by Ag. A potentially therapeutic bispecific human Fc␥-Fc chimera, called GE2, was constructed and shown to inhibit class switching to IgE and IgE production by human B cells (21) and mediator release from FcRI-expressing dendritic cells (22). GE2 also attenuated allergen-dependent activation of human cord blood-derived mast cells and peripheral blood basophils, and allergen skin tests in monkeys (23,24).…”
mentioning
confidence: 99%